A community-based, medical student-led walking and education program was associated with a reduction in frailty levels among adults with elevated frailty - O’Brien, Myles W.; Wilson, Taylor M.; Cheema, Muhammad; Zafar, Zainab; Choi, Minji; Shivgulam, Madeline E.; Theou, Olga (Frontiers in Aging, 2025)
ObjectivesFrailty reflects the accumulation of health deficits that an individual develops over their lifespan. Walk with a Future Doc (WWAFD) is a medical student-led, community-based education and walking program. We examine the impact of a 12-week WWAFD program on lowering the frailty levels in a New Brunswick community and if the effects of the program would be specific to those with higher pre-WWAFD frailty levels.MethodsEighty participants (age: 41–85 years; 51 female individuals) were recruited from the YMCA in New Brunswick (Canada) via word-of-mouth, social media, and consulting local physicians. The inclusion criteria were broad. All community members were welcome to attend the program, but only those over age 18 and those that attended ≥6/12 walks were included in the study. Participants were grouped into non-frail (FI< 0.10; n = 51) and very mild + frail (FI ≥ 0.10; n = 29) groups for comparison. Participants attended a student-led 1-h/week health education and walking program and completed the Canadian Longitudinal Study on Aging Frailty Index (FI) questionnaire before and after the program.ResultsFrailty was unchanged pre-to-post-intervention in the non-frail group (0.053 ± 0.030 to 0.056 ± 0.029, p = 0.475) but reduced in the very mild + frail group (0.166 ± 0.075 to 0.153 ± 0.066, p = 0.014).Conclusion and implicationsThe WWAFD program that included weekly walking and education sessions was associated with reduced frailty levels among adults with FI ≥0.10. This change emphasizes the value of community-based physical activity programs and exemplifies the impact they can have on the participants’ health outcomes.